A decision-making model for supporting selection of green building materials - Al-Atesh, E.A. (Taylor and Francis Ltd., 2021)
The manufacture and use of building materials result in numerous environmental concerns in the construction industry. Green building materials (GBMs) are environmentally friendly compared to their traditional counterparts. However, identifying the criteria for selecting GBMs and assessing their sustainability have been challenging. In this study, the Analytic Hierarchy Process (AHP) technique was used to decide between selecting steel building structure and reinforced concrete (RC) building structure as an alternative. In the first phase, the criteria for selecting GBMs were identified through literature review, expertsâ opinions, and questionnaire survey. In the second phase, the purposive sampling technique was used to select experts and professionals in materials selection to compare the different GBMs criteria and also, to compare and weight the provided alternatives. The findings of this study identified that 29 criteria were ranked using a scatter plot of means and standard deviation scores. Besides, the results indicated that RC building structure, with a weight value of 0.5225, was a better alternative to steel building structure. Additionally, the results show that the environmental and economic criteria are more important than the social criteria. This study, therefore, developed a decision-making model for helping stakeholders to select materials required to achieve sustainable buildings. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.